Beyond memory T cells: mechanisms of protective immunity to tuberculosis infection. Issue 7 (23rd June 2019) - Steigler, Pia; Verrall, Ayesha J; Kirman, Joanna R
Abstract: Tuberculosis (TB) is a serious infectious disease caused by infection with Mycobacterium tuberculosis, and kills more people annually than any other single infectious agent. Although a vaccine is available, it is only moderately effective and an improved vaccine is urgently needed. The ability to develop a more effective vaccine has been thwarted by a lack of understanding of the mechanism of vaccine‐induced immune protection. Over recent decades, many novel TB vaccines have been developed and almost all have aimed to generate memory CD4 T cells. In this review, we critically evaluate evidence in the literature that supports the contention that memory CD4 T cells are the prime mediators of vaccine‐induced protection against TB. Because of the lack of robust evidence supporting memory CD4 T cells in this role, the potential for B‐cell antibody and "trained" innate cells as alternative mediators of protective immunity is explored. Abstract : In this review, we critically evaluate evidence in the literature that supports the contention that memory CD4 T cells are the prime mediators of vaccine‐induced protection against Tuberculosis. Because of the lack of robust evidence supporting memory CD4 T cells in this role, the potential for B cells and "trained" innate cells immunity as alternative mediators of protective immunity is explored.